Organisational culture at higher educational institutions: The importance of internal marketing - Kyriacou, Evdoxia; Panigyrakis, George G. (My University, 2020)
To fulfil their mission to provide high-quality services, higher education institutions are required to conduct internal marketing. This paper draws on the case study of a University in Cyprus to explore how six interconnected dimensions of internal marketing inform the satisfaction and loyalty of administrative staff. The study adopts a quantitative methodology, using a survey questionnaire to collect data. The questionnaire was answered online by a sample of 47 administrative employees. Descriptive statistics, correlations and a multiple linear regression analysis were performed. The study presents findings and results of quantitative analysis and proposes an internal marketing model. Limitations and future research proposals are discussed.
Keywords: Higher education; Human resources; Internal culture; Internal marketing; Organisational culture; Quality services; Value system